2020
DOI: 10.3390/md18040189
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Secretory Expression and Characterization of a Unique pH-Stable and Cold-Adapted Alginate Lyase

Abstract: Cold-adapted alginate lyases have unique advantages for alginate oligosaccharide (AOS) preparation and brown seaweed processing. Robust and cold-adapted alginate lyases are urgently needed for industrial applications. In this study, a cold-adapted alginate lyase-producing strain Vibrio sp. W2 was screened. Then, the gene ALYW201 was cloned from Vibrio sp. W2 and expressed in a food-grade host, Yarrowia lipolytica. The secreted Alyw201 showed the activity of 64.2 U/mL, with a molecular weight of approximate 38.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 33 publications
2
50
0
Order By: Relevance
“…The specific activity of purified Alyw202 toward sodium alginate was 1926.4 U/mg, while those toward polyG blocks and polyM blocks were 2132.2 and 1074.6 U/mg, respectively. These specific activities were much higher than those of Alyw201 [ 13 ]. The results indicated that Alyw202 may be a more efficient tool for alginate degradation.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…The specific activity of purified Alyw202 toward sodium alginate was 1926.4 U/mg, while those toward polyG blocks and polyM blocks were 2132.2 and 1074.6 U/mg, respectively. These specific activities were much higher than those of Alyw201 [ 13 ]. The results indicated that Alyw202 may be a more efficient tool for alginate degradation.…”
Section: Resultsmentioning
confidence: 97%
“…As mentioned in our previous study, Vibrio sp. W2 was screened from the viscera of abalone using alginate as the sole carbon source at 25 °C [ 13 ]. During the 48 h fermentation in ASC liquid medium at 25 °C, alginate lyase activity was observed in culture supernatants, while no alginate-degrading activity was detcted in the collected intact cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations